Mind the Remoteness! Income disparities across Japanese Prefectures - López Rodríguez, Jesús; Nakamura, Daisuke (Estudios de Economía, 2016)
In this paper we analyze the role played by Market access to explain income disparities among Japanese Prefectures for different periods of time. The results of the estimations suggest that 1) Market access plays an important role in the explanation of income disparities in Japan, 2) the effect of Market access is robust to the inclusion of control variables considered important in the explanation of the Japanese income disparities, 3) the estimations show a tendency for the Market access variable to lose explanatory power throughout the time. In this 10 year time span analyzed from 1996 to 2005 the decrease in explanatory power of Market access was around 15%.